Pre-puberal children and exercise in hot and humid environments: A brief review - Sinclair, W. H.; Crowe, M. J.; Spinks, W. L.; Leicht, A. S. (Journal of Sports Science & Medicine, 2007)
The ability of pre-pubertal children to regulate their body temperature under thermoneutral environments is similar to that of an adult albeit via differing routes. However, this ability is challenged when exposed to extreme environments. Thermoregulatory responses of pre-pubertal children differ from adults via adaptations that occur during growth and maturation and disadvantage children when exercising in hot and humid environments. When ambient temperatures exceed that of the skin, an influx of thermal energy from the environment increases thermal stress. When coupled with exercise, the increased thermal stress results in reduced physical performance and an increased risk of developing heat-related illness. Evidence suggesting the severity of heat-related illness is greater in pre-pubertal children than adults is inconclusive because age-related differences in thermoregulatory responses are attributed to either morphologic or functional changes. Additionally, the majority of research on pre-pubertal children exercising in the heat has been maturational or comparative studies with adults conducted in the near absence of convective cooling, complicating extrapolation to field-based environments. However, current consensus is that pre-pubertal children are disadvantaged when exercising in extreme temperatures and that care should be taken in preparing for and conducting sporting activities in hot and humid environments for pre-pubertal children.